2022
DOI: 10.3389/fbioe.2021.789621
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin Adherent Cell Populations Derived From Avascular and Vascular Regions of the Meniscus Have Enhanced Clonogenicity and Differentiation Potential Under Physioxia

Abstract: The meniscus is composed of an avascular inner region and vascular outer region. The vascular region has been shown to contain a progenitor population with multilineage differentiation capacity. Strategies facilitating the isolation and propagation of these progenitors can be used to develop cell-based meniscal therapies. Differential adhesion to fibronectin has been used to isolate progenitor populations from cartilage, while low oxygen or physioxia (2% oxygen) enhances the meniscal phenotype. This study aime… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 53 publications
(99 reference statements)
1
8
0
Order By: Relevance
“…Recently, Kitahashi et al [10] identified several molecules deemed essential to promoting adhesion, proliferation, and PG production of MSCs injected into the knee joint. More recently, Pattappa et al [17] studied the importance of FN in the isolation of progenitor cells from the meniscus and its potential utility in cell‐based therapies for meniscal tears or defects. All these investigations, among others [11], lead us to think that MSCs cannot fix the PU scaffold on their own.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kitahashi et al [10] identified several molecules deemed essential to promoting adhesion, proliferation, and PG production of MSCs injected into the knee joint. More recently, Pattappa et al [17] studied the importance of FN in the isolation of progenitor cells from the meniscus and its potential utility in cell‐based therapies for meniscal tears or defects. All these investigations, among others [11], lead us to think that MSCs cannot fix the PU scaffold on their own.…”
Section: Discussionmentioning
confidence: 99%
“…Based on differential adhesion to fibronectin [39,43,44,72], we were able to isolate progenitor cell populations from both the inner and outer zone of the meniscus. MPCs maintained their capacity to generate meniscal-like tissue upon serial passage, making them a particularly attractive cell source for meniscus TE strategies where large numbers of cells are required to fabricate human scale tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Using a differential adhesion to fibronectin protocol that has been used to isolate progenitor cells from the articular cartilage [40][41][42], it is possible to isolate cellular subpopulations from within the meniscus which have a high proliferative capacity and are able to maintain their differentiation potential after serial subculture, unlike non-fibronectin selected meniscus cells [43]. Phenotypically distinct progenitor cells have been found in both the inner and outer regions of the meniscus, which retain distinct capabilities to differentiate into inner and outer meniscus fibroblasts with limited evidence of hypertrophy [44]. Therefore, integrating such meniscus progenitor cells (MPCs) into advanced biofabrication strategies could potentially enable the engineering of functional meniscus constructs that mimic the spatial composition of the native tissue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic principles of the progenitor cells isolation protocol used in this study are based on the selection of cells that highly express β1 integrins and demonstrate rapid adhesion to extracellular matrix proteins ( Jones and Watt, 1993 ), which was originally used for chondroprogenitors isolation ( Williams et al, 2010 ). KorSimilar et al ( Korpershoek et al, 2021 ) and Pattappa et al ( Pattappa et al, 2022 ) also used the fibronectin selective protocol to isolate meniscus progenitor cells. However, we included a direct comparison of the protocol for the efficiency of donor-matched chondrocyte, avascular and vascular meniscus progenitor isolation, and present these results for the first time (to our knowledge).…”
Section: Discussionmentioning
confidence: 99%